2019
DOI: 10.1186/s12885-019-6064-8
|View full text |Cite
|
Sign up to set email alerts
|

Unmet needs and related factors of Korean breast cancer survivors: a multicenter, cross-sectional study

Abstract: Background Identification of specific needs in patients with cancer is very important for the provision of patient-centered medical service. The aim of this study was to investigate the unmet needs and related factors of Korean breast cancer survivors. Methods A multicenter, cross-sectional, interview survey was performed among 332 Korean breast cancer survivors. The Comprehensive Needs Assessment Tool for cancer patients was administered to survivors who gave written i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
51
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(62 citation statements)
references
References 29 publications
10
51
1
Order By: Relevance
“…Our results were close to those of Santin et al's study (2015) [15], which suggested that the inability to meet needs of these patients could reduce their QoL. Our results were also similar to a previous study revealing that survivors of Korean breast cancer with QoL problems reported a higher degree of supportive care needs [38]. Thus, satisfying colorectal cancer survivors' supportive care needs could lower their level of depression and anxiety and increase their QoL.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our results were close to those of Santin et al's study (2015) [15], which suggested that the inability to meet needs of these patients could reduce their QoL. Our results were also similar to a previous study revealing that survivors of Korean breast cancer with QoL problems reported a higher degree of supportive care needs [38]. Thus, satisfying colorectal cancer survivors' supportive care needs could lower their level of depression and anxiety and increase their QoL.…”
Section: Discussionsupporting
confidence: 90%
“…Results of our research were similar to those of previous studies that indicated that patients who completed treatment recently had high supportive care needs [32] and that anxiety was associated with supportive care needs and QoL in breast cancer survivors [40]. Our results were also similar to results of a previous study on factors influencing supportive care needs of breast cancer survivors in South Korea [38]. This means that supportive care needs of cancer survivors may increase immediately after treatment because of anxiety about new changes, although it is believed that supportive care needs are decreased as patients adapt to life [41].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Among physicians, the level of unmet needs of Korean breast cancer survivors was perceived to be highest in the hospital service domain, whereas Korean breast cancer survivors reported the highest unmet needs in the information and education domain [ 17 ]. In other words, while survivors reported greater unmet needs for information about methods for overcoming their disease or recurrence, physicians perceived survivors as having higher needs for shorter waiting times before treatment, rehabilitation, or psychological services.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several quantitative studies on the psychosocial difficulties and unmet needs of Korean cancer survivors [6,7]. However, quantitative studies have limitations in identifying unmet needs, as respondents' voices and experiences are not covered intimately.…”
Section: Introductionmentioning
confidence: 99%